Sistem Pendukung Keputusan Pemilihan Rumah di Kawasan Cepu Menggunakan Analytical Hierarchy Process - Widyassari, Adhika Pramita; Yuwono, Teguh (Universitas Nusantara PGRI Kediri, 2019)
Strategies to buy a house, consumers often experience problems in determining the house to be purchased, because each house has different characteristics. These characteristics will be used as reference considerations in determining which house to buy. In this study, the AHP (Analytical Hierarchy Process) method was used to weight the criteria and test the level of consistency with the pairwise comparison matrix. If the matrix has been consistent, then it can be continued to rank to determine the chosen alternative by using input weighting criteria obtained from the AHP method. To overcome the above problems, it is necessary to build a decision support system by implementing a ranking that can make it easier to determine House Selection using the AHP (Analytical Hierarchy Process) method. Of the 9 sample houses in the Cepu area, the highest was the Housing of Zam Zam Cepu Type 38/78 with a total value of 2,84564719.